Hydrogen-Bonding Affords Sustainable Plastics with Ultrahigh Robustness and Water-Assisted Arbitrarily Shape Engineering - Gong, Kai (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.